Country-specific chemical signatures of persistent organic pollutants (POPs) in breast milk of French, Danish and Finnish women. (November 2016) - Antignac, J.P.; Main, K.M.; Virtanen, H.E.; Boquien, C.Y.; Marchand, P.; Venisseau, A.; Guiffard, I.; Bichon, E.; Wohlfahrt-Veje, C.; Legrand, A.; Boscher, C.; Skakkebæk, Niels E.; et al.
Abstract: The present study compares concentrations and chemical profiles of an extended range of persistent organic pollutants (dioxins, polychlorobiphenyls, brominated flame retardants and organochlorine pesticides) in breast milk samples from French (n = 96), Danish (n = 438) and Finnish (n = 22) women. Median exposure levels observed in French women (WHO-TEQ2005 PCDD/F = 6.1 pg/g l.w., WHO-TEQ2005 dl-PCB = 4.3 pg/g l.w., sum of 6 ndl-PCB = 85.2 ng/g l.w., sum of 7 i-PBDE = 1.5 ng/g l.w.) appeared overall lower than in Danish and Finnish women for all examined POPs, except for α-HBCD (2-fold higher level at 0.6 ng/g l.w.). Furthermore, the observed exposure levels of dioxins and PCBs were higher in Danish women (WHO-TEQ2005 PCDD/F = 13.2 pg/g l.w., WHO-TEQ2005 dl-PCB = 6.6 pg/g l.w., sum of 6 ndl-PCB = 162.8 ng/g l.w.) compared to Finnish women (WHO-TEQ2005 PCDD/F = 9.0 pg/g l.w., WHO-TEQ2005 dl-PCB = 4.6 pg/g l.w., sum of 6 ndl-PCB = 104.0 ng/g l.w.), whereas the concentrations of PBDEs were similar for Danish and Finnish women (sum of 7 i-PBDE = 4.9 and 5.2 ng/g l.w. respectively). The organochlorine (OC) pesticide contamination profile, determined in a subset of French samples, was dominated by p, p'-DDE (56.6%), followed by β-HCH (14.2%), HCB (9.7%) and dieldrin (5.2%), while other compounds were only minor contributors (<5%). The three countries appeared to be discriminated by the observed contamination patterns of the PCDD/F versus PCB, and the 1, 2, 3, 6, 7, 8-HxCDD versus 1, 2, 3, 4, 7, 8-HxCDD ratios, in addition to the relative contributions of specific congeners to the contamination profile (PCBs #118 and #156, PBDEs #28, #47, #99 and #153). In conclusion, unique chemical signatures were observed for each country on the basis of some POP congeners. Future biomonitoring studies will need to consider the high variability of individual exposure profiles in relation to multiple exposure sources but also physiological and metabolic differences. Highlights: A set of 78 POPs was determined in Danish, Finish and French breast milk samples. Exposure levels appeared lower in French women except for α-HBCD. Country-specific exposure patterns were observed among the analyzed samples. Lifestyle, genetic polymorphisms and metabolism factors may explain these patterns. Abstract : Specific internal exposure patterns are observed in terms of POP contamination profiles in breast milk of Danish, Finish versus French women.